2008
DOI: 10.1111/j.1460-9592.2008.02675.x
|View full text |Cite
|
Sign up to set email alerts
|

Subhypnotic propofol infusion plus dexamethasone is more effective than dexamethasone alone for the prevention of vomiting in children after tonsillectomy

Abstract: For children undergoing tonsillectomy, intraoperative subhypnotic propofol infusion combined with dexamethasone treatment provides a better prophylaxis against postoperative vomiting than does dexamethasone alone.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 30 publications
0
23
1
Order By: Relevance
“…Several studies have demonstrated that propofol has antiemetic properties, including when administered in the subhypnotic dose range [128]. Low dose intraoperative propofol infusion (bolus of 1 mg/kg followed by an infusion of 20 µg kg −1 min −1 ), has been shown to reduce PONV when used by itself or when combined with other antiemetics [129, 130]. Also, small doses of propofol used as rescue therapy (20mg as needed) has been found to be as effective as ondansetron [131].…”
Section: ) Other Advantages Of Propofol Tivamentioning
confidence: 99%
“…Several studies have demonstrated that propofol has antiemetic properties, including when administered in the subhypnotic dose range [128]. Low dose intraoperative propofol infusion (bolus of 1 mg/kg followed by an infusion of 20 µg kg −1 min −1 ), has been shown to reduce PONV when used by itself or when combined with other antiemetics [129, 130]. Also, small doses of propofol used as rescue therapy (20mg as needed) has been found to be as effective as ondansetron [131].…”
Section: ) Other Advantages Of Propofol Tivamentioning
confidence: 99%
“…Administration of steroids to patients undergoing tonsillectomy or adenoidectomy has been found to reduce postsurgical nausea, vomiting and pain, although it may also increase postsurgical bleeding [9,11]. Similarly, the ability of short acting intravenous anesthetics plus steroids to prevent postsurgical nausea and vomiting has been assessed in children undergoing tonsillectomy or adenoidectomy [4], but less is known about the association between anesthetic agents and bleeding after tonsillectomy. A meta-analysis showed that the concentrations of coagulation factors prior to surgery did not predict postsurgical bleeding [2].…”
Section: Discussionmentioning
confidence: 98%
“…To minimize postsurgical complications, most tonsillectomies are performed with the patient under general anesthesia and in a supine position [4]. While some patients undergo tonsillectomy alone, others also undergo other types of surgery at the same time.…”
Section: Introductionmentioning
confidence: 99%
“…However, pain on injection of propofol may be uncomfortable to an awakening patient. Erdem et al [5] reported that intraoperative infusion of 20 µg/kg/min of propofol had a prophylactic antiemetic effect. Another study showed that 1.0 mg/kg of propofol at the end of surgery reduced both PONV and emergence agitation in children [6].…”
Section: Discussionmentioning
confidence: 99%
“…Propofol has been reported to be an effective antiemetic at low doses in patients undergoing anticancer therapy [3] and surgery [4,5,6] in many articles, but the precise mechanism by which propofol works as an antiemetic is unclear [2]. In this study, we evaluated the preventive antiemetic efficacy of different doses of propofol administered 15 minutes before the end of surgery without delaying emergence in middle aged females undergoing laparoscopic gynecologic surgery and receiving opioid-based intravenous patient controlled analgesia (PCA).…”
Section: Introductionmentioning
confidence: 99%